2005
DOI: 10.1007/s10969-005-2664-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Expression and Purification of Membrane Proteins by SUMO Fusion in Escherichia coli

Abstract: Severe acute respiratory syndrome coronavirus (SARS-CoV) membrane protein and 5-lipoxygenase-activating protein (FLAP) are among a large number of membrane proteins that are poorly expressed when traditional expression systems and methods are employed. Therefore to efficiently express difficult membrane proteins, molecular biologists will have to develop novel or innovative expression systems. To this end, we have expressed the SARS-CoV M and FLAP proteins in Escherichia coli by utilizing a novel gene fusion e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 17 publications
1
69
1
3
Order By: Relevance
“…Our result suggested that Trx fusion partner was a superior fusion tag in enhancing buforin IIb expression solubility. Our result was contrary to a previous report that also suggested that subtraction purification with affinity chromatography was particularly useful for the production of small peptides, as they were easily lost during purification with non-affinity chromatographic methods (Loll 2003;Zuo et al 2005). Besides, because of the toxicity and the high cost of IPTG, lactose is a promising inducer in the lacpromotor based expression system.…”
Section: Discussioncontrasting
confidence: 99%
“…Our result suggested that Trx fusion partner was a superior fusion tag in enhancing buforin IIb expression solubility. Our result was contrary to a previous report that also suggested that subtraction purification with affinity chromatography was particularly useful for the production of small peptides, as they were easily lost during purification with non-affinity chromatographic methods (Loll 2003;Zuo et al 2005). Besides, because of the toxicity and the high cost of IPTG, lactose is a promising inducer in the lacpromotor based expression system.…”
Section: Discussioncontrasting
confidence: 99%
“…When used as an N-terminal carrier protein during prokaryotic expression, SUMO promotes folding and structural stability, which leads to enhanced functional production compared to untagged protein [48][49][50][51][52][53][54]. Unlike GST and MBP, SUMO does not itself serve as a means for purification of fusion proteins; however, the His 6 in series with the SUMO tag has been established to facilitate purification of fusion proteins.…”
Section: Small Ubiquitin-related Modifier (Sumo)mentioning
confidence: 99%
“…Fusion to SUMO has been shown to enhance the expression of recombinant proteins in Escherichia coli (Malakhov et al 2004;Butt et al 2005;Zuo et al 2005;Marblestone et al 2006;Panavas et al 2008), while fusion to hSUMO3 led to similar enhancement in E. coli (data not shown) and Pichia pastoris (R.J. Peroutka, D. Roy, J. Strickler, and T.R. Butt, in prep.).…”
Section: Introductionmentioning
confidence: 85%
“…Paradoxically, lysine residues in target proteins that are SUMOylated are protected from ubiquitylation, while SUMOylation of proteins can also serve as a signal for ubiquitylation (Prudden et al 2007). Thus, nature has evolved two pathways that have remarkably similar mechanical and biochemical features, yet have very distinct roles in cellular physiology (Johnson 2004).Fusion to SUMO has been shown to enhance the expression of recombinant proteins in Escherichia coli (Malakhov et al 2004;Butt et al 2005;Zuo et al 2005;Marblestone et al 2006;Panavas et al 2008), while fusion to hSUMO3 led to similar enhancement in E. coli (data not shown) and Pichia pastoris (R.J. Peroutka, D. Roy, J. Strickler, and T.R. Butt, in prep.).…”
mentioning
confidence: 99%